Bureaucratic Reform Strategy to Realize Quality Digital Public Services - Zulfan Nahruddin (Generasi Sains Indonesia, 2024)
The proposed qualitative research paper will examine the strategies, challenges and perceptions of stakeholders in relation to the bureaucratic reform with the aim of improving digital public services. The paper establishes the efficiency of digital reforms such as the encouragement of the inclusive participation and the elimination of resistance to change through thorough interviews with the stakeholders, namely the government officials and information technology professionals. The results indicate that there is a sharp issue of organizational inertia and that it is critical to have clear evaluation measurements, which will help in the effective provision of digital services. Further, the perception of the stakeholders indicates that there is a great faith in the ability of digital public services to enhance access to government, efficiency and transparency in the government administration. Nevertheless, the success of such initiatives can be derailed, unless the root causes of such obstacles are considered and different stakeholders are involved in the reform process. The research is significant in that it adds to the existing body of literature on the need to comprehend human factors in digital transformation of public services, and highlights key role of promoting organisational culture of collaboration in public agencies. The experiences gained during this research are useful to policymakers and practitioners who work to overcome the challenges of the digital reform in the governmental setting and eventually improve the processes of service delivery and social trust.